Chemical Synthesis of Modularly Modified Analogs of E2/NS1 Peptides on a Novel Chemically and Mechanically Stable Terpolymer of 1,6-Hexanediol Diacrylate, N-Vinylpyrrolidone on Styrene Support - Jacob, Sunil; Harry, Nissy Ann; Binoj, Kunju Kunju; Tharayil, Tharamma George; Satyakeerthy, Thonduparambil Ravindran; John, Sosamma (Trends in Sciences, 2023)
Analysis of the chemokine analogs synthesised on a terpolymer-polystyrene, N-vinylpyrrolidone, 1,6-hexanediol diacrylate crosslinked resin (PS-NVP-HDDA) showed it can be used a good solid support for the chemical synthesis of polypeptides. The polymer with a good swelling character and chemical resistance was synthesised by the radical aqueous suspension polymerisation technique. HPLC analysis of the crude peptides synthesised on PS-NVP-HDDA resin showed that it is a better substitute for most of the currently available polymer support for peptide synthesis. HIGHLIGHTS This article includes the synthesis of modularly modified analogs of E2/NS1 peptides The synthesized peptide is IIe-Phe-Thr-Tyr-His-Phe-Asn-Ser-Ser-Ser-Gly-Cys(Acm)-Pro-Glu-Ala-Asp-Leu-Asp- Cys(Acm)-Arg-Ser-Lys-Leu-Arg The peptide is synthesized on a chemically and mechanically stable terpolymer of 1,6-hexanediol diacrylate, N-vinylpyrrolidone on styrene support The polymer exhibited a good swelling character and chemical resistance The peptide was synthesized with great purity GRAPHICAL ABSTRACT